FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN PEDICULOSIS CAPITIS DI SMP DARUL HIJRAH PUTRI MARTAPURA: CASE CONTROL STUDY - Musafaah; Yunida, Sovia; Rachmawati, Kurnia (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2016)
Pediculosis capitis is an infestation caused by pediculus humanus var. capitis and it is one ofhealth problem on children who lived in a dormitory. Unfortunately, recent research about thingscaused head louse is still limited. The objective was to determine the factors which hadcorrelation with pediculosis capitis incident in children who lived in dormitory. The method ofthis research used case control study, performed to girl students in SMP Pondok Pesantren on 09December 2015. Respondents were divided into 2 groups, case group (n=48) and control group(n=48). The examination of head louse was performed using tight-brush comb and patient’sresponse has written in checklist paper. The result there was no correlation between hair long(p=0,321), frequency of hair washing in a week (p=0,117), shared comb (p=0,301), shared towel(p=1,000), shared head cover (jilbab) (p=0,323), sleep habit or shared bed (p=0,784), andfrequency of changing bed cover once a week (p=0,268), with pediculosis capitis incident. It canbe concluded this study there was no correlation between factors with pediculosis capitisincidence, this happened maybe because of other factor like occupancy density.